2004
DOI: 10.1103/physrevb.70.184419
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial strain measurements ofSrRuO3SrMnO3magnetic multilayers

Abstract: Magnetic multilayers of (SrRuO 3 ) m (SrM nO 3 ) n were grown artificially using the pulsed laser deposition technique on (001)-oriented SrT iO 3 substrates.The state of strain at the interfaces and the structural coherency are studied in details utilizing asymmetrical X-ray diffraction and the sin 2 ψ method.First, the evolution of the lattice parameters, the crystallinity and the epitaxy of the films are evaluated as a function of the number of SrM nO 3 unit cells using X-rays diffraction and transmission el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 30 publications
6
43
0
Order By: Relevance
“…The observed negligibly small changes in the low field moments at low temperature and the increase in the paramagnetic moments with LCMO layer thickness could be due to the C-type CO state of the constituents. The well defined Curie temperature and H C of the trilayer on LAO is due to the formation of the magnetic domain at the interfaces which is evidenced from ZFC/FC magnetic properties of the multilayer structure that have more interfaces [10]. The magnetization of the trilayer on STO and LAO increases gradually with the increase in magnetic field and does not show a clear saturation.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The observed negligibly small changes in the low field moments at low temperature and the increase in the paramagnetic moments with LCMO layer thickness could be due to the C-type CO state of the constituents. The well defined Curie temperature and H C of the trilayer on LAO is due to the formation of the magnetic domain at the interfaces which is evidenced from ZFC/FC magnetic properties of the multilayer structure that have more interfaces [10]. The magnetization of the trilayer on STO and LAO increases gradually with the increase in magnetic field and does not show a clear saturation.…”
mentioning
confidence: 85%
“…In our earlier studies, we have found the evidence of ferromagnetic phase and the enhanced coercive field in the superlattices consisting of two antiferromagnets La 0.5 Ca 0.5 MnO 3 (LCMO) and Pr 0.5 Ca 0.5 MnO 3 (PCMO) grown on (001) oriented LaAlO 3 (LAO) [10]. In this article, we report the studies on the structure, magnetization and transport properties of the trilayer, where various thicknesses of LCMO layer sandwiched between two PCMO layers with different fixed thicknesses, simultaneously grown on (001) oriented LAO and SrTiO 3 (STO).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic structure based on 3d -transition metal compounds exhibit overdamped oscillatory exchange coupling [1,2,3], unidirectional magnetic anisotropy such as horizontal/vertical magnetic hysteresis loop shifts [4,5,6,7] and enhanced coercivity [8,9]. In antiferromagnetic(AFM)/ferromagnetic(FM) heterostructures the coercivity and unidirectional anisotropy are enhanced, in contrast to corresponding free magnetic multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In previous articles, the multilayer consisting of FM SrRuO 3 (SRO) and AFM SrMnO 3 (SMO) were grown to study the exchange coupling [6,7] at the interfaces of SRO and SMO.…”
Section: Introductionmentioning
confidence: 99%